Exile - Taslima Nasrin (Penguin, 2016)
On 21 November 2007, the city of Kolkata came to a rude, screeching halt as a virulent mob of religious fanatics took to the streets. Armed with a fatwa from their ideologues, the mob demanded that Taslima Nasrin leave the city immediately. While the police stood watching, mere dumb witnesses to such hooliganism, a morally, intellectually and politically bankrupt Left Front government, tottering under the strain of their thirty-year-old backward-looking rule, decided to ban her book and drive her out of the city she has always considered her second home.